Pemetaan Prediksi Erosi Tanah pada Litologi Breksi Argopura Lereng Gunung Argopura dengan Pendekatan Survai Menggunakan Metode USLE dan SIG - Basuki Basuki; Tri Wahyu Saputra; Laily Mutmainnah; Tri Candra Setiawati; Marga Mandala; Vega Kartika Sari (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2024)
Soil erosion is the loss of land or part of the land from one place to another due to water and wind factors. Land use on the slopes of Mount Argopura has been partly converted to seasonal crops and plantation crops, especially sugar cane. There have been changes, such as in the rainy season, when water flowing into the downstream areas is murky, carrying thick mud. This condition indicates that soil erosion is occurring. The aim of the research is to assess and predict the hazard level of soil erosion in mountainous area of Argopura with the lithology of the Argopura breccia by using the Universal Soil Loss Equation (USLE) method and geographic information systems (GIS). The results showed that the  mountainous area of Argopura is mostly covered by the heavy category area, with soil loss of 180–480 tons/ha/year and an area distribution reaching 1,502.49 ha (37.59%). The distribution in the heavy category was found in land use type of moorland and paddy fields, both irrigated and rainfed. The potential for soil erosion in the very heavy category with a soil loss rate of >480 tons/ha/year covers an area of 508.52 ha (12.72%). The very heavy category is partly due to the use of jungle land and steep slopes, so cultivation carried out on this land needs to be replaced with plant conservation, which can reduce soil erosion.